0117 Management of epistaxis: A pilot simulation programme. (2nd November 2015) - Photiou, Dana; Smith, Derek; Wet, Du Toit De; Stewart, Ian; Dewar, Alastair; Hathorn, Iain
Abstract : Background: Epistaxis is a common Ear, Nose and Throat (ENT) emergency, accounting for 33% of admissions to Scottish ENT units. 1, 2 It also imposes high demands on Emergency Medicine. 1 Junior doctors have limited experience in its management, compromising patient safety especially in hospitals with no on-site ENT cover. 3, 4 We developed a simulated 'skills-and-drills' pilot for EM and ENT junior doctors and nurses on the management of epistaxis, benefiting trainees and improving patient safety. 3–6 Methodology: Candidates were recruited from ENT and EM departments. There was an initial skills station on nose-packing and cautery. The simulation then focused on management of epistaxis, resuscitation and warfarin reversal through a three-stage scenario design: actor with simulated epistaxis for initial presentation and history-taking; SimMan3G for resuscitation; and a practical training model for nose-packing and cautery. Faculty provided technical support, clinical skills training, and facilitated debriefing. Questionnaires at the end of teaching assessed pre and post-session confidence and clinical relevance on a five-point Likert-scale. Outcomes: There were 10 participants (1 EM doctor, 2 ENT doctors, 1 EM nurse, 1 ENT nurse, 5 medical and nursing students). Mean pre-simulation confidence in managing epistaxis was 2.2. Post-teaching, this increased to 4.1. Rating for topic relevance was 4.3. Candidates enjoyed the hands on, realistic and MDT approach of the course, particularly the opportunity to safely practice technical interventions. Nursing participants felt the simulation could expand on the nursing role in epistaxis management. 100% of the candidates stated they would recommend the programme to colleagues. Potential impact: Simulated epistaxis management is effective in improving confidence and knowledge of nasal packing procedures in a safe environment. 4, 6 This can be taught through a multi-disciplinary approach. The nursing elements will be expanded in future sessions. Simulation will be included in departmental inductions in NHS Lothian, and clinical impact will be assessed by audit. References: Walker TWM, et al . The epidemiology and chronobiology of epistaxis: an investigation of Scottish hospital admissions 1995-2004. Clin Otolaryngol. 2007;32:361–365 Kucik CJ, Clenney T. Management of epistaxis. Am Fam Physician. 2005;71(2):305–11 Maher S, et al . Training on management of ENT emergencies using low-fidelity nasal simulator. Int Res J Med Sci. 2013;1(10):1–6 Malekzadeh S, et al . ORL emergencies boot camp: using simulation to onboard residents. Laryngoscope. 2011;121(10):2114–21 List RJ, et al . Anterior nasal packing simulators. Clin Otolaryngol. 2011;36: 593–594 Rudolph JW, et al . Establishing a safe container for learning in simulation: the role of the presimulation briefing. Simulat Healthc. 2014;9(6):339–49